Diffusion and assimilation of government microblogging - Ma, Liang. (2013)
Internationally, the public sector is adopting social media applications (e.g. Twitter and social networking services (SNS)) to harness cutting-edge information technology (IT) developments, but we know little about what drives the diffusion of these applications. In this paper, I adapt the Berry–Berry policy and innovation diffusion model to explain the diffusion and assimilation of government microblogging, supplementing its four dimensions (learning, competition, upper-tier mandate and public pressure) with organizational resources and capacity. Data on 282 prefecture-level cities in China are employed to test several theoretical hypotheses empirically. Horizontal competition is found to be significantly and positively associated with the assimilation of government microblogging, although the other three dimensions are found not to be its key antecedents. Consistent with the study's hypotheses, the results support the significantly positive effects of fiscal resources and IT capacity. Municipal wealth, size and administrative ranking are also positively and significantly correlated with the number of government microblogs.